REMOVAL OF ANTIBIOTIC EMERGING POLLUTANTS: AN OVERVIEW - Palacio, Daniel A.; Aranda, Francisca L.; Rivas, Bernabe L (Journal of the Chilean Chemical Society, 2022)
In recent decades the presence of pollutants has grown considerably around the world, along with the scarcity of fresh water. One of the environmental problems that has intensified lately is the presence of antibiotic resistant strains and the appearance of resistant genes due to the misuse and high worldwide consumption of this type of pharmaceutical products. Therefore, the number of investigations has been intensified to address these great problems that can affect public health and cause great economic losses around the world. For this reason, in this review, different antibiotics removal techniques in water have been compiled and analyzed critically.